Gödel's theorem : an incomplete guide to its use and abuse - Franzén, Torkel (A K Peters, 2005)
"Among the many expositions of Gödel's incompleteness theorems written for non-specialists, this book stands apart. With exceptional clarity, Franzén gives careful, non-technical explanations both of what those theorems say and, more importantly, what they do not. No other book aims, as his does, to address in detail the misunderstandings and abuses of the incompleteness theorems that are so rife in popular discussions of their significance. As an antidote to the many spurious appeals to incompleteness in theological, anti-mechanist and post-modernist debates, it is a valuable addition to the literature." -- John W. Dawson, author of Logical Dilemmas: The Life and Work of Kurt Gödel.